2003
DOI: 10.1016/s0886-3350(03)00226-8
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral dislocation of in-the-bag posterior chamber intraocular lenses in a patient with intermediate uveitis

Abstract: We present a case of bilateral dislocation of in-the-bag intraocular lenses (IOLs) in a patient with intermediate uveitis. The IOLs dislocated into the vitreous cavity 24 and 41 months postoperatively. A complete pars plana vitrectomy with sutured posterior chamber IOL implantation was performed after each dislocation. The final visual acuity was 20/20(-) in each eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…Careful review of the literature revealed 72 subsequent cases (Table 1). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Several case series reporting the management of IOL dislocation included a small number of ''in-the-bag dislocated lenses'' without presenting further information and thus were not included in the present review. 28,29 The exact incidence of this complication is not known.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Careful review of the literature revealed 72 subsequent cases (Table 1). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Several case series reporting the management of IOL dislocation included a small number of ''in-the-bag dislocated lenses'' without presenting further information and thus were not included in the present review. 28,29 The exact incidence of this complication is not known.…”
Section: Incidencementioning
confidence: 99%
“…Pseudoexfoliation was the most common, accounting for more than 50% of cases. Other common conditions were uveitis, 7,21,23 trauma, 11,16,23 vitrectomy, 12,21,23 and increased axial length. 11,17 One or more mechanisms may have resulted in postoperative capsule dislocation: preoperative zonular weakness, surgical trauma to the zonules, capsule contraction syndrome, and postoperative trauma.…”
Section: Proposed Mechanismsmentioning
confidence: 99%
“…Intraocular lens dislocations can be divided into in-the-bag and out-of-the-bag with correspondingly different etiologies. [1][2][3] The most common etiologies for in-the-bag dislocation are pseudoexfoliation and prior vitreoretinal surgery, whereas out-of-the-bag dislocation usually occurs because of capsule rupture during cataract surgery. Intraocular lens dislocation may be immediate (out-of-the-bag dislocation) or may develop months or years after surgery (in-thebag dislocation).…”
Section: Jcrs Online Case Reports 2015; 3:1-3 Q 2015 Ascrs and Escrsmentioning
confidence: 99%
“…Although malpositioning of the intraocular lens (IOL) is rare in the modern cataract surgery era, but several predisposing conditions like pseudoexfoliation [1,2], uveitis [3,4], trauma [5] or anterior capsular phimosis can lead to either subluxation or dislocation of bag-IOL complex [6]. In contrast to IOL dislocation, bag dislocation occurs as a result of progressive zonular dehiscence even after years of uneventful surgery.…”
Section: Introductionmentioning
confidence: 99%